Modern conceptions of etiology and pathogenesis of benign breast disease: the possibilities of pathogenetic treatment - Vladimir G Bespalov; Elizaveta I Kovalevskaya (IP Berlin A.V., 2019)
Relevance. The review article is devoted to modern conceptions of etiology and pathogenesis of benign breast disease (BBD), a common female pathology, as well as the pathogenetic treatment of BBD. Aim. Substantiation of the new possibilities of the pathogenetic treatment of BBD. Materials and methods. It was conducted the analysis of domestic and world literature in the following areas: etiology, pathogenesis, treatment of BBD, prevention of breast cancer (BC). Results. Dozens of etiological factors of various natures cause BBD: genetic, reproductive, hormonal, gynecological diseases, extragenital pathology, environment and lifestyle, medical interventions. The etiological factors of BBD mostly coincide with the risk factors of BC. The lack of progesterone, the predominance of estradiol and chronic hyperestrogenemia, leading to hyperproliferation of the ductal and lobular epithelium of the mammary glands, underlie the pathogenesis of BBD. The pathogenesis of proliferative forms of BBD and BC have common features. In patients with proliferative and precancerous forms of BBD, the risk of BC increases significantly. Chronic iodine deficiency is one of the common pathogenetic pathways for the development of BBD. The drug mamoclam containing organically bound iodine from laminaria thallus is an effective and safe remedy for the pathogenetic treatment of BBD. Conclusion. Pathogenetic treatment of BBD not only improves the quality of life of patients, but also reduces the risk of BC.